A preliminary analysis of mergers and acquisitions by Microsoft from 1992 to 2016: A resource and competence perspective - Ali Jose Lopez Giron; Pierre Vialle (International Telecommunications Society (ITS), 2017)
Merger and acquisitions (M&A) have been a frequently used growth mode in the ICT Industry during the last two decades. They did so for several reasons, such as expanding the scale and scope of their business or acquire new capabilities Microsoft is highly representative of those ICT firms who have intensively relied on M&A for growth. Microsoft since its foundation has acquired around 200 companies; in average 6 companies per year and has targeted different sectors of the ICT business. Up to the authors' knowledge, no exhaustive analysis of the acquisitions made by Microsoft over a long period has been made, in particular with a focus on Resources and Competence. In this paper, we aim at identifying the patterns behind the acquisition of numerous companies made by Microsoft since 1992, in terms of end-product, type of business, core product, resource and competences. We put a particular emphasis on the resource and competence acquired through these deals. By document research, we have been able to collect relevant information on 178 acquisitions between 1992 and 2016. In this paper, we present the methodology we have followed and some preliminary results. We conclude by discussing possible research extensions based on the current research.
Keywords: 330; Merger and acquisitions; resource and competence; strategy; Microsoft